2012
DOI: 10.1258/vasc.2011.oa0336
|View full text |Cite
|
Sign up to set email alerts
|

Blood loss and complications following carotid endarterectomy in patients treated with clopidogrel

Abstract: This study assessed the effect of uninterrupted antiplatelet therapy on perioperative blood loss and complications in patients undergoing carotid endarterectomy. The files of 107 consecutive patients (mean age 69.5 ± 9 years; range 47-88; 78 men) who underwent carotid endarterectomy were reviewed. Twenty-six patients had been treated with clopidogrel (16 of whom were on combined clopidogrel and aspirin treatment) and compared with non-clopidogrel patients. Antiplatelet treatment was continued until the day of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 37 publications
(86 reference statements)
2
22
1
Order By: Relevance
“…In eight cases with revision surgery (40%) the patients were treated with clopidrogel perioperatively, five patients with a monotherapy and three in combination with ASA. Our results on an increased risk for revision surgery under clopidrogel perioperatively are in accordance with some [19,24] and contrary to some other [6,22] previous studies. The inconsistent data might be contributory to insufficient numbers of patients and different study design.…”
Section: Discussionsupporting
confidence: 89%
“…In eight cases with revision surgery (40%) the patients were treated with clopidrogel perioperatively, five patients with a monotherapy and three in combination with ASA. Our results on an increased risk for revision surgery under clopidrogel perioperatively are in accordance with some [19,24] and contrary to some other [6,22] previous studies. The inconsistent data might be contributory to insufficient numbers of patients and different study design.…”
Section: Discussionsupporting
confidence: 89%
“…In literature, some studies reported high major and minor complications rates due to small number of patients included. [25][26][27] Stone et al indicated that rate of bleeding that required re-operation due to clopidogrel use was 0.05% in 5264 CEA patients while bleeding due to clopidogrel and ASA combination was 1.5% and this rate was similar to the rate found in patients that did not use any antiaggregant therapy. However, bleeding due to use of ASA alone was 1.3%.…”
Section: Discussionmentioning
confidence: 80%
“…24 Forty nine percent of our CEA patients received ASA while 37% were on both ASA and clopidogrel therapy, and this rate was higher when compared to some smaller studies. [25][26][27] This may be related due to cautious approach of the authors to use clopidogrel. The vascular study group in The United Kingdom also agree with use of clopidogrel and its combinations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 Neither the incidence of clinically important neck haematoma 14 16 nor the morbidity rate from haemorrhagic complications increases in patients undergoing CEA taking clopidogrel with or without aspirin. 17 Surgery may take longer; 18 however, careful consideration should be given to the risks and benefits of performing regional anaesthesia in these patients. 19 There is no evidence available in the literature on the safety of performing CEA under GA or regional anaesthesia techniques in patients receiving newer, faster onset and offset antiplatelet drugs such as ticagrelor or prasugrel or any other of the newer oral anticoagulants.…”
Section: Preoperative Assessmentmentioning
confidence: 99%